IMPULSE: the impact of gender on the presentation and management of aortic stenosis across Europe - Steeds, Richard Paul; Messika-Zeitoun, David; Thambyrajah, Jeetendra; Serra, Antonio; Schulz, Eberhard; Maly, Jiri; Aiello, Marco; Rudolph, Tanja K; Lloyd, Guy; Bortone, Alessandro Santo; Clerici, Alberto; Delle-Karth, Georg; et al. (Open heart, 2021)
AIMS: There is an increasing awareness of gender-related differences in patients with severe aortic stenosis and their outcomes after surgical aortic valve replacement (SAVR) and transcatheter aortic valve implantation (TAVI). METHODS: Data from the IMPULSE registry were analysed. Patients with severe aortic stenosis (AS) were enrolled between March 2015 and April 2017 and stratified by gender. A subgroup analysis was performed to assess the impact of age. RESULTS: Overall, 2171 patients were enrolled, and 48.0% were female. Women were characterised by a higher rate of renal impairment (31.7 vs 23.3%; p<0.001), were at higher surgical risk (EuroSCORE II: 4.5 vs 3.6%; p=0.001) and more often in a critical preoperative state (7.0vs 4.2%; p=0.003). Men had an increased rate of previous cardiac surgery (9.4 vs 4.7%; p<0.001) and a reduced left ventricular ejection fraction (4.9 vs 1.3%; p<0.001). Concomitant mitral and tricuspid valve disease was substantially more common among women. Symptoms were highly prevalent in both women and men (83.6 vs 77.3%; p<0.001). AVR was planned in 1379 cases. Women were more frequently scheduled to undergo TAVI (49.3 vs 41.0%; p<0.001) and less frequently for SAVR (20.3 vs 27.5%; p<0.001). CONCLUSIONS: The present data show that female patients with severe AS have a distinct patient profile and are managed in a different way to males. Gender-based differences in the management of patients with severe AS need to be taken into account more systematically to improve outcomes, especially for women.
Keywords: Registries; Sex Factors; aortální stenóza; endovascular procedures; Humans; registrace; transcatheter aortic valve replacement; Female; rizikové faktory; Aged; věkové faktory; aortic valve stenosis; senioři; lidé; Aortic Valve Stenosis; Europe; Transcatheter Aortic Valve Replacement; Heart Valve Prosthesis; časové faktory; sexuální faktory; transkatetrální implantace aortální chlopně; Follow-Up Studies; ženské pohlaví; stupeň závažnosti nemoci; Male; Retrospective Studies; incidence; Incidence; Aged, 80 and over; Severity of Illness Index; senioři nad 80 let; srdeční chlopně umělé; retrospektivní studie; Age Factors; Risk Assessment; mužské pohlaví; aortální chlopeň; Time Factors; hodnocení rizik; Evropa; následné studie; Aortic Valve; Risk Factors